A new perspective on word order preferences: the availability of a lexicon triggers the use of SVO word order - Marno, Hanna; Langus, Alan; Omidbeigi, Mahmoud; Asaadi, Sina; Seyed-Allaei, Shima; Nespor, Marina (Frontiers in Psychology, 2015)
Word orders are not distributed equally: SOV and SVO are the most prevalent among the world’s languages. While there is a consensus that SOV might be the ‘default’ order in human languages, the factors that trigger the preference for SVO are still a matter of debate. Here we provide a new perspective on word order preferences that emphasizes the role of a lexicon. We propose that while there is a tendency to favor SOV in the case of improvised communication, the exposure to a shared lexicon makes it possible to liberate sufficient cognitive resources to use syntax. Consequently SVO, the more efficient word order to express syntactic relations, emerges. To test this hypothesis, we taught Italian (SVO) and Persian (SOV) speakers a set of gestures and later asked them to describe simple events. Confirming our prediction, results showed that in both groups a consistent use of SVO emerged after acquiring a stable gesture repertoire.